Damage Recovery Method for Air–Sea Cross-Domain Communication Network Based on Improved Dijkstra and Load Balancing - Zhigang Shang; Hongyu Zhang; Jing Yang (Applied Sciences)
With the complexity of the future battlefield and the increasing demand for multi-domain operations, the importance of air–sea cross-domain communication networks is rising. Communication technology connecting air and sea faces many challenges: for example, multi-node failure may lead to network partition, communication interruption and even task failure. Therefore, research on the multi-node failure recovery method of air–sea cross-domain communication networks has become an urgent need to ensure their stability and mission continuity. This paper proposes a link selection strategy based on an improved Dijkstra algorithm and load balancing on the basis of link quality prediction. The simulation results show that the algorithm can effectively achieve network recovery.